Prediction of Future Computers Using Developing Technologies - Yaser Rahimi (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
Previous predictions about future of computers, such as Moore’s law are analyzed, at first. Then developments in basic science such as quantum physics, spintronics, and also developments in technologies such as biology, nanoelectronics, photonics and nanophotonics, communications technologies, and medical engineering that are applicable in computers, are introduced. Then expected future goals are discussed: Reduction of cost and weight, increase of processing speed, increase of intelligence and integration with other systems.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.4726